Does the Implementation of Multidisciplinary Developmental Care Rounds Increase the Utilization of Developmental Caregiving Interventions in the Neonatal Unit?. Issue 2 (April 2023) - Muirhead, Renee; Bates, Amanda
Abstract : Aims: The aims of this project were to improve the utilization of developmental care practices in the neonatal unit and to increase opportunities for parental involvement in the planning and provision of caregiving. Methods: This implementation project was conducted in a 79-bed neonatal tertiary referral unit in Australia. A pre/postimplementation survey design was utilized. A preimplementation survey was conducted to collect data on staff's perceived perception of developmental care practices. Following analysis of the data, a process for multidisciplinary developmental care rounds was developed and then implemented across the neonatal unit. A postimplementation survey was then conducted to evaluate whether staff perceived any changes in developmental care practices. The project was conducted over 8 months. Results: A total of 97 surveys (pre: n = 46/post: n = 51) were received. Differences were demonstrated in staff's perceived perception of developmental care practices between the pre- and postimplementation periods in 6 themes of developmental care practice. Identified areas of improvement included the use of the 5-step dialogue, encouragement of parents to contribute to care planning, availability of a well-defined care plan for parents to visualize and document caregiving activities, increased use of swaddled bathing, side-lying position for nappy changes, consideration of infants sleep state before caregiving, and increased use of skin-to-skin therapy for management of procedural pain. Conclusion: Despite the majority of staff members who participated in both surveys acknowledging the importance of family-centered developmental care practice on neonatal outcomes, their use in clinical care is not always considered or practiced. Although it is reassuring to see improvements in several areas of developmental care postimplementation of the developmental care rounds, continued awareness and reinforcement of developmental neuroprotective caregiving strategies through initiatives such as a multidisciplinary care rounds are warranted.